Improving The Economic Utility of Durian Seeds as One of the UMKM Products of Sunti Village, Serbajadi Aceh - Dayyan, Muhammad; Zamzami, Muhammad (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2024)
Durian is one of the plants that has many benefits and can also be processed into various types of products that can add economic value to be developed in Sunti Village. Community service activities through the Melayu Serumpun Real Work Lecture (KKN) program. Group 13 KKNMS Of The Sunti Village got the idea to make durian Seed Chips as a sunti Village UMKM Product, This idea was distributed to the sunti village Community. Because durian seed chips have good potential, prospects and market value. The methods used for the implementation of making durian seed chips products are discussion, training and evaluation of activity results. Processed durian seed chips will be one of the UMKM products from Sunti Village. Where this can be an additional income for the people of Sunti Village whose income comes from their fields. The purpose of making these durian chips is an effort to improve UMKM from Sunti Village.